Love story [compact disc, unabridged] : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family, 2017)
Decades ago, John and Elizabeth Baxter lived a love story that is still playing out in the lives of their adult children and grandchildren. But few of them know the exact details of that love story or the heartbreak that brought the two together. Now in high school, Ashley Baxter Blake's oldest son, Cole, must write a family history paper for a freshman English class. He decides to interview his grandfather about that long ago distant love story.